Characteristics of Soil Fertility Affecting the Rice Fields Productivity in Bogor Regency - Yunus Arifien; Sari Anggarawati (Universitas Sembilanbelas November Kolaka, 2019)
The purpose of this study was to determine the parameters of soil fertility in rice fields and the effect of soil fertility on paddy productivity in Bogor Regency. This research was conducted in the districts of Cileungsi, Darmaga and Leuwiliang, Bogor Regency. The location selection was done deliberately based on the location of rice production facilities with Ciherang and Inpari varieties. Sampling was conducted at several sampling points at each location. Each sub-district was taken 8 samples or 24 in total, then analyzed in the laboratory. Data processing using multiple regression with a dummy. The results showed that the soil in Bogor Regency was generally acidic, where soil fertility characteristics with organic C content were low to moderate, nitrogen was very low to moderate, P was low to high, K was very low to moderate, CEC was moderate to high, and saturation bases (KB) are moderate to high. Soil biology, namely total bacteria, total fungi, total solvent P bacteria, Azotobacter sp., And Rhizobium sp. Are generally low to moderate. Variable characteristics of soil fertility in the form of organic C, Nitrogen (N), K2O HCl 25%, and CEC significantly influence rice productivity. Soil fertility in the three districts is almost the same and does not affect the productivity of rice fields. While the productivity of rice fields with Inpari varieties is higher than those grown by Ciherang varieties. To increase the productivity of rice fields in Bogor Regency, it is recommended to plant Inpari variety rice by applying N fertilizer